2003
DOI: 10.1051/0004-6361:20031031
|View full text |Cite
|
Sign up to set email alerts
|

The HELLAS2XMM survey

Abstract: Abstract. We present results from the photometric and spectroscopic identification of 122 X-ray sources recently discovered by XMM-Newton in the 2-10 keV band (the HELLAS2XMM 1dF sample). Their flux cover the range 8 × 10 −15 −4 × 10 −13 erg cm −2 s −1 and the total area surveyed is 0.9 square degrees. One of the most interesting results (which is found also in deeper sourveys) is that about 20% of the hard X-ray selected sources have an X-ray to optical flux ratio (X/O) ten times or more higher than that of o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
416
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 247 publications
(470 citation statements)
references
References 46 publications
53
416
1
Order By: Relevance
“…The region where most of unobscured Sy2 are found (i.e. X/O < −1) is usually populated by normal galaxies or low-luminosity AGN (Fiore et al 2003). This result confirms the decreasing contrast between the AGN light and the host starlight for the unobscured Sy2, suggesting the dilution hypothesis is possible if the BEL are weak.…”
Section: Dilution By the Host Galaxysupporting
confidence: 71%
“…The region where most of unobscured Sy2 are found (i.e. X/O < −1) is usually populated by normal galaxies or low-luminosity AGN (Fiore et al 2003). This result confirms the decreasing contrast between the AGN light and the host starlight for the unobscured Sy2, suggesting the dilution hypothesis is possible if the BEL are weak.…”
Section: Dilution By the Host Galaxysupporting
confidence: 71%
“…in the 2-10 keV energy range), even if exhibiting signatures of photoelectric absorption, is less attenuated (see e.g. Fiore et al 2003). Obscured QSOs are therefore expected to display large values of X-ray to optical flux ratio, defined here as:…”
Section: The Exo50 Samplementioning
confidence: 99%
“…For a fixed absorption or AGN/host ratio, the higher is the redshift, the higher is the f x / f o and the redder are the optical-to-infrared colours (cf. Fiore et al 2003). However from a deeper look to the data, this redshift effect alone is not able to explain the extreme properties of all the EXO50 objects; for example the source number 5 (namely 2XMMJ123204.9+215254 at z=0.76) can not be explained with the redshift effect but requires very high AGN/host ratios; a very high AGN/host galaxy ratio indeed may be required also for 2XMMJ100038.9+050955 and 2XMMJ135055.7+642857 (sources 2 and 6, respectively) if their redshifts turn out to be similar to that of 2XMMJ123204.9+215254.…”
Section: Are the Exo50 Type 2 Qso Objects Different From Standard X-rmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of the Chandra and XMM data, there have been a number of computations of the evolution of the HXLF with redshift (e.g., Cowie et al 2003;Steffen et al 2003;Ueda et al 2003;Hasinger 2003;Fiore et al 2003;Barger et al 2005), while Sazonov & Revnivtsev (2004) have used the RXTE data to compute the local 3-20 keV luminosity function. The latest HXLF determinations by Barger et al (2005) use only the spectroscopically identified X-ray sources with L 2−8 keV = 10 42 ergs s −1 in the CDF-N, CDF-S, and CLASXS fields.…”
Section: Evolution Of the Hard X-ray Luminosity Functionmentioning
confidence: 99%